Determination of 8 sweeteners and ethyl carbamate in Baijiu by ultra performance liquid chromatography-tandem mass spectrometry - ZHANG Jianhui, YU Qiong, WANG Xin, HU Shaowu, SUN Yanping, HUANG Jing, ZHANG Yu, CHEN Xidong (Zhongguo niangzao, 2024)
A method was established for the determination of ethyl carbamate (EC) and 8 kinds of sweeteners (sucralose, saccharin sodium, cyclamate, acesulfame potassium, aspartame, neotame, alitame, stevioside) in Baijiu by ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). The Baijiu samples were filtered by 0.22 μm organic filter film and directly injected for mass spectrometry, separated using Agilent ZORBAX RRHD Eclipse Plus C18 column (100 mm×2.1 mm, 1.8 μm) with gradient elution of methanol and 0.1% acetic acid aqueous solution, column temperature 40 ℃ and flow rate 0.35 ml/min, and detected by switching between positive and negative ion modes using ULPC-MS/MS. The injection time was 9 min. The results showed that 9 tested substances had a good linear relationship in the range of 2-500 μg/L, the correlation coefficients (R2) were all greater than 0.997, the detection limits were 0.1-0.4 μg/L, and the recoveries were 92.6%-108.7% under the spiked levels of 100 μg/L, and the relative standard deviations (RSD) were lower than 2%. The detection method had the advantages of simple pretreatment, good reproducibility, high sensitivity and fast analysis, and could be used for rapid detection and daily monitoring of EC and 8 kinds of sweeteners in Baijiu.